ISSUES OF DIGITALIZATION OF TAX POLICY IN A MARKET ECONOMY - Turayev Alijon Akmal o'g'li; Qurbanov Azimjon Xasanovich; Qurbonov Jaxongir Ibroximjonovich (Лучшие интеллектуальные исследования, 2023)
Abstract: The article examines the influence of digital technologies on taxation processes in a modern market economy. We analyze changes in tax policy caused by the introduction of digital innovations, and also consider possible ways to optimize tax processes using modern technologies. The article also discusses the problems and challenges that states face when digitalizing the tax system, and offers recommendations for effective adaptation to new conditions.